Health education: the role and functions of the specialist and the generalist Educação em saúde: papel e funções do especialista e do generalista - Helen P. Cleary (Universidade de São Paulo, 1988)
Education for health is a process in which all public health and medical care personnel are involved. People learn both formally (planned learning experiences) and informally (unplanned learning experiences). Since the patient, the client, the consummer and the community expect public health and medical care personnel to assist them with health and disease issues and problems, the response of the professional "educates" the customer whether the professional intends to educate or not. Therefore, it is incumbent on all public health and medical care professionals to understand their educational functions and their role in health education. It is also important that the role of the specialist in education be clear. The specialist, as to all other specialists, has an in-depth knowledge of his area of expertise, i.e., the teaching/learning process; s/he may function as a consultant to others to enhance the educational potential of their role or s/he may work with a team or with communities or groups of patients. Specific competencies and knowledge are required of the health education specialist; and there is a body of learning and social change theory which provides a frame of reference for planning, implementing and evaluating educational programs. Working with others to enhance their potential to learn and to make informed decisions about health/disease issues is the hallmark of the health education specialist. A Educação em Saúde é um processo no qual todo o pessoal da saúde pública e do atendimento médico estão envolvidos. As pessoas aprendem ou formalmente (experiências de aprendizagem planejadas) ou informalmente (experiências de aprendizagem não planejadas). Na medida em que o paciente, o cliente, o usuário e a comunidade esperam que o pessoal da saúde pública e o pessoal do atendimento médico os auxiliem, no que diz respeito a assuntos e a problemas da saúde, a resposta do profissional "educa" o usuário, quer o profissional tenha ou não tenha a intenção de o fazer. Portanto, cabe a todos os profissionais da saúde pública e do atendimento médico entender suas funções educativas e seu papel na Educação em Saúde. É também importante que o papel do especialista em educação esteja claro. O especialista, tanto quanto os outros especialistas, possui um profundo conhecimento na sua área técnica como, por exemplo, o processo de ensino-aprendizagem; pode trabalhar como um consultor para ampliar o potencial educativo de outros ou pode trabalhar com equipes, com comunidades ou com grupos de pacientes. É preciso que o especialista em Educação em Saúde tenha conhecimentos e competências específicos e há um conjunto de teorias de aprendizagem e de mudança social que proporcionam um esquema de referência para planejar, implementar e avaliar programas educativos. Trabalhar com pessoas para ampliar seu potencial quanto à aprendizagem e a tomar decisões informadas a respeito de assuntos relacionados à saúde/doença é o objetivo do especialista em Educação em Saúde.